Human Purkinje in silico model enables mechanistic investigations into automaticity and pro-arrhythmic abnormalities. (May 2020) - Trovato, Cristian; Passini, Elisa; Nagy, Norbert; Varró, András; Abi-Gerges, Najah; Severi, Stefano; Rodriguez, Blanca
Abstract: Cardiac Purkinje cells (PCs) are implicated in lethal arrhythmias caused by cardiac diseases, mutations, and drug action. However, the pro-arrhythmic mechanisms in PCs are not entirely understood, particularly in humans, as most investigations are conducted in animals. The aims of this study are to present a novel human PCs electrophysiology biophysically-detailed computational model, and to disentangle ionic mechanisms of human Purkinje-related electrophysiology, pacemaker activity and arrhythmogenicity. The new Trovato2020 model incorporates detailed Purkinje-specific ionic currents and Ca 2+ handling, and was developed, calibrated and validated using human experimental data acquired at multiple frequencies, both in control conditions and following drug application. Multiscale investigations were performed in a Purkinje cell, in fibre and using an experimentally-calibrated population of PCs to evaluate biological variability. Simulations demonstrate the human Purkinje Trovato2020 model is the first one to yield: (i) all key AP features consistent with human Purkinje recordings; (ii) Automaticity with funny current up-regulation (iii) EADs at slow pacing and with 85% hERG block; (iv) DADs following fast pacing; (v) conduction velocity of 160 cm/s in a Purkinje fibre, as reported in human. The human in silico PCs population highlights that: (1) EADs are caused by ICaL reactivation in PCs with large inward currents; (2) DADs and triggered APs occur in PCs experiencing Ca 2+ accumulation, at fast pacing, caused by large L-type calcium current and small Na + /Ca 2+ exchanger. The novel human Purkinje model unlocks further investigations into the role of cardiac Purkinje in ventricular arrhythmias through computer modeling and multiscale simulations. Graphical abstract: Unlabelled Image Highlights: A human in silico AP model was developed to investigate arrhythmia in cardiac Purkinje. The new Purkinje model enables multiscale investigations from single cell to tissue. Populations of human Purkinje models reproduce and explain experimental variability. Ca 2+ -current reactivation triggers EADs in virtual Purkinje cells with weak repolarisation reserve. Ca 2+ accumulation caused by increased Ca 2+ and NCX currents triggers DADs.